Pengaruh Knowledge Sharing, Team Work, dan Keterampilan Kerja Terhadap Kinerja Karyawan Owabong Park Purbalingga - Topan Chaya Gumelar; Alfato Yusnar Kharismasyah; Suyoto; Dian Widyaningtyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test knowledge sharing, team work and work skills on the performance of Owabong Park Purbalingga employees. This research uses a quantitative method by distributing questionnaires to obtain as complete information as possible regarding the influence of knowledge sharing, team work and work skills on employee performance through Owabong Park Purbalingga employees. The population of this study was 112 permanent employees of Owabong Park Purbalingga. The data analysis method used is SEM with the smart PLS version 3.0 tool. The tests used are outer model, inner model test, and hypothesis test. The results of this research show that knowledge sharing, team work and work skills have a significant positive influence on employee performance.